KNOWLEDGE SHARING SEBAGAI PENDUKUNG CUSTOMER RELATIONSHIP MANAGEMENT PADA COFFEE SHOP TANAKA - Elly Rahayu; Wan Mariatul Kifti; Daril Khoir Nasution (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The increasing competition in the coffee shop industry requires businesses to establish sustainable customer relationships through the implementation of Customer Relationship Management (CRM). One factor that supports effective CRM is Knowledge Sharing, defined as the practice of employees sharing information and knowledge with customers during service interactions. This study aims to examine the effect of Knowledge Sharing on Customer Relationship Management at Coffee Shop Tanaka. A quantitative approach was employed involving 100 customers selected using purposive sampling. Data were collected through a five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that Knowledge Sharing has a positive and significant effect on Customer Relationship Management, with a path coefficient of 0.758, a T-statistic of 14.217, and a p-value of 0.000. Furthermore, the R² value of 0.575 indicates that Knowledge Sharing explains 57.5% of the variance in Customer Relationship Management. These findings demonstrate that employees' knowledge-sharing practices enhance customer interaction, strengthen trust, and foster long-term customer relationships. This study provides empirical evidence that Knowledge Sharing serves as an important strategy in supporting the implementation of Customer Relationship Management within the coffee shop industry. Keywords: Knowledge Sharing; Customer Relationship Management; Coffee Shop: PLS-SEM; Management.   Abstrak: Persaingan industri coffee shop menuntut pelaku usaha untuk membangun hubungan pelanggan yang berkelanjutan melalui penerapan Customer Relationship Management (CRM). Salah satu faktor yang diduga mendukung keberhasilan CRM adalah Knowledge Sharing, yaitu praktik berbagi pengetahuan yang dilakukan karyawan kepada pelanggan selama proses pelayanan. Penelitian ini bertujuan menganalisis pengaruh Knowledge Sharing terhadap Customer Relationship Management pada Coffee Shop Tanaka. Penelitian menggunakan pendekatan kuantitatif dengan melibatkan 100 pelanggan sebagai responden yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui kuesioner menggunakan skala Likert lima poin dan dianalisis menggunakan Partial Least Squares Structural Equation Modeling (PLS-SEM) dengan aplikasi SmartPLS 4. Hasil penelitian menunjukkan bahwa Knowledge Sharing berpengaruh positif dan signifikan terhadap Customer Relationship Management dengan koefisien jalur sebesar 0,758, nilai T-statistics sebesar 14,217, dan p-value sebesar 0,000. Nilai R² sebesar 0,575 menunjukkan bahwa Knowledge Sharing mampu menjelaskan 57,5% variasi Customer Relationship Management. Temuan ini menunjukkan bahwa praktik berbagi pengetahuan yang dilakukan karyawan kepada pelanggan mampu meningkatkan kualitas interaksi, membangun kepercayaan, dan memperkuat hubungan jangka panjang dengan pelanggan. Penelitian ini memberikan kontribusi empiris mengenai peran Knowledge Sharing sebagai strategi pendukung implementasi Customer Relationship Management pada industri coffee shop. Kata kunci: Knowledge Sharing; Customer Relationship Management; Coffee Shop; PLS-SEM; Manajemen.